Early detection of breast cancer: the utilization of mammography in Germany - Anne Starker; Klaus Kraywinkel; Ronny Kuhnert (Journal of Health Monitoring, 2017)
Breast cancer is the most common cancer in women in Germany. In addition to physical examinations (palpation) mammographies are offered every two years to women aged 50 to 69 years as part of the mammography screening programme. For this purpose women are invited in writing and recive a leaflet with information about the background, aims procedures, benefits and possible disadvantages that the screening programme might have. The invitation and the leaflet were revised in 2015 to better support the invited women in making an informed decision about whether they should participate in the programme. In the GEDA 2014/2015-EHIS study, the respondents provided the date of their last mammography and the reason for this. A mammography has been performed on 74.2% of women aged 50 to 69 years within the last two years. 80.7% of these women stated that the reason for this was an invitation sent out by the national screening programme.